2013
DOI: 10.3168/jds.2013-6831
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Caseins and the casein micelle: Their biological functions, structures, and behavior in foods

Abstract: A typical casein micelle contains thousands of casein molecules, most of which form thermodynamically stable complexes with nanoclusters of amorphous calcium phosphate. Like many other unfolded proteins, caseins have an actual or potential tendency to assemble into toxic amyloid fibrils, particularly at the high concentrations found in milk. Fibrils do not form in milk because an alternative aggregation pathway is followed that results in formation of the casein micelle. As a result of forming micelles, nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
240
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(280 citation statements)
references
References 166 publications
9
240
1
11
Order By: Relevance
“…potentially amyloid fibrilforming α-synuclein, to return to its natively unfolded (intrinsically disordered) state (Cox et al 2014;Treweek et al 2015). From our other studies, it is apparent that the unrelated molecular chaperones, clusterin, caseins and 14-3-3ζ, all exhibit a very similar mechanism of ATP-independent sHsp-like chaperone action (Carver et al 2003;Holt et al 2013;Thorn et al 2015;Williams et al 2011). In E. coli, curli proteins (e.g.…”
Section: The N-and C-terminal Flanking Regions In Shspsmentioning
confidence: 90%
See 1 more Smart Citation
“…potentially amyloid fibrilforming α-synuclein, to return to its natively unfolded (intrinsically disordered) state (Cox et al 2014;Treweek et al 2015). From our other studies, it is apparent that the unrelated molecular chaperones, clusterin, caseins and 14-3-3ζ, all exhibit a very similar mechanism of ATP-independent sHsp-like chaperone action (Carver et al 2003;Holt et al 2013;Thorn et al 2015;Williams et al 2011). In E. coli, curli proteins (e.g.…”
Section: The N-and C-terminal Flanking Regions In Shspsmentioning
confidence: 90%
“…One explanation for sHsp oligomerisation is that it may protect against fibril formation, for example, within the ACD, in addition to the protection provided by the unstructured flanking regions. Other protein oligomers associate for such a reason, as we have shown for the unstructured milk casein proteins in which micelle (oligomer) formation by the four unrelated caseins (either with themselves individually, or with other caseins, or all of them to form the casein micelle in milk) prevents amyloid fibril formation by κ-and α s2 -casein via mutual chaperone interaction and also (principally within the casein micelle) by the chaperone action of the β-and α s1 -caseins (Holt et al 2013;Holt and Carver 2012;Thorn et al 2015). Similarly, transthyretin fibril formation requires initial dissociation from a tetrameric species prior to a conformational change within the monomer which leads to an aggregation-prone intermediate (Colon and Kelly 1992).…”
Section: Oligomerisation Of Shspsmentioning
confidence: 98%
“…The formed nanoclusters with a core of ACP surrounded by casein molecules assemble to casein micelles. These structures ensure supersaturation of calcium and phosphate in milk without calcification (57,58). Similar sequestration of ACP as calcium phosphate nanoclusters was demonstrated for OPN peptides suggesting that such nanoclusters of other secreted phosphoproteins might be involved in the inhibition of calcification in soft and mineralized tissues, the extracellular matrix or biofluids (59).…”
mentioning
confidence: 81%
“…Our reviews showed how exciting new ways of thinking about caseins and casein micelles are possible. They have proved popular with many casein researchers, as was recognised in 2016 when the review article published in this journal (Holt et al, 2013) was given the ADSA Most-Cited Paper Award in the Dairy Foods section. In the process of developing our argument some long-established notions about the nature of caseins were re-evaluated, among which was the relative importance of the hydrophobic effect in casein-casein interactions.…”
Section: Response To Horne and Luceymentioning
confidence: 99%
“…In 2013, we wrote a review in the Journal of Dairy Science (Holt et al, 2013) and another in the International Dairy Journal in 2015 (Thorn et al, 2015), both dealing with the application of modern protein science concepts to the chemistry and physics of caseins. These were substantial documents with an important message.…”
Section: Response To Horne and Luceymentioning
confidence: 99%